2018
DOI: 10.1080/1354750x.2018.1474261
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers of hypertrophy and fibrosis in patients with hypertrophic cardiomyopathy assessed by cardiac magnetic resonance

Abstract: Although no correlation between sST2 levels and myocardial fibrosis was found, sST2 may provide some additional information about hypertrophy extension. NT-proBNP and hs-cTnT are useful biomarkers in assessment of hypertrophy and fibrosis in HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
6
22
1
1
Order By: Relevance
“…Left ventricular hypertrophy, LAE or both were associated with significantly increased NT‐proBNP concentrations in cats with HCM in our study. Similar findings have been described previously in cats, 12,14,15 dogs, 34 and people 42‐44 . The POCT had similar SE and SP as did the ELISA for diagnosing HCM in cats, which is in agreement with previous studies in which SE of the tests ranged between 71%‐92% and SP between 94%‐100% for detecting cardiac disease 12,14,15 .…”
Section: Discussionsupporting
confidence: 90%
“…Left ventricular hypertrophy, LAE or both were associated with significantly increased NT‐proBNP concentrations in cats with HCM in our study. Similar findings have been described previously in cats, 12,14,15 dogs, 34 and people 42‐44 . The POCT had similar SE and SP as did the ELISA for diagnosing HCM in cats, which is in agreement with previous studies in which SE of the tests ranged between 71%‐92% and SP between 94%‐100% for detecting cardiac disease 12,14,15 .…”
Section: Discussionsupporting
confidence: 90%
“…One study demonstrated that only the hs-cTnI was an independent indicator of the presence of LGE [14]. On the contrary, another study revealed that Nt-proBNP, not hs-cTnI, was strongly correlated with the amount of LGE [15]. And the present study not only showed that the serum levels of Nt-proBNP were correlated with the LGE% in multivariate analyses, but also was useful for the detection of myocardial brosis.…”
Section: Discussionsupporting
confidence: 41%
“…The above differences in the relationship between the circulating biomarkers and the LGE% may be due to the different study populations and methods of quantifying LGE with CMR. Speci cally, in line with the study by Kawasaki et al [16] our study excluded patients with LVEF < 50%, whereas the other two studies did not [14,15]. Additionally, previous studies usually used the visual scoring or semiquantitative scoring method [14,27], and the 2SD thresholding method was used in Kawasaki's study [16].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations